Eosinophilic Cystitis Presenting as Possible Pediatric Rhabdomyosarcoma in Conventional Imaging Including 18F-FDG-PET/CT/MRI—A Rare Case - Naja Enevold Olsen (Diagnostics, 2021)
Eosinophilic cystitis (EC) is a relatively rare, but benign inflammatory bladder disease compared to that of the malignant pediatric rhabdomyosarcoma (RMS), in which it can be mimicking on initial suspicion. The origin, symptoms and findings of both EC and RMS are still discussed and hence, lead to the challenge in distinguishing them by cystoscopy and several image modalities. We present a case in which cross-sectional imaging modalities including fluorine-18-fluro-2-deoxy-D-glucose (18F-FDG)-positron emission tomography (PET) / computed tomography (CT) / magnetic resonance imaging (MRI) (18F-FDG-PET/CT/MRI (The imaging modality 18F-FDG-PET/CT/MRI referring to two continuous scans scanned on the same 18F-FDG-tracer dose for both the whole-body 18F-FDG-PET/CT and the regional 18F-FDG-PET/MRI of the pelvis.)) raised suspicion of RMS. Hence, the final diagnosis of EC was established by repeated histopathology. It is important to have EC in mind when seeking differential diagnosis of malignant diseases like RMS in order to provide the correct treatment for the patient and highly homogenously increased 18F-FDG-uptake should raise the suspicion of EC as a differential diagnosis. Furthermore, 18F-FDG-uptake rate is suggested as a future potential biomarker for monitoring of therapeutic response in eosinophilic inflammatory diseases, thus more research on this topic is needed.